2015
DOI: 10.1371/journal.pone.0130666
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of T Cell Lymphomas in Carbon Ion-Irradiated Mice Reveals Frequent Interstitial Chromosome Deletions: Implications for Second Cancer Induction in Normal Tissues during Carbon Ion Radiotherapy

Abstract: Monitoring mice exposed to carbon ion radiotherapy provides an indirect method to evaluate the potential for second cancer induction in normal tissues outside the radiotherapy target volume, since such estimates are not yet possible from historical patient data. Here, male and female B6C3F1 mice were given single or fractionated whole-body exposure(s) to a monoenergetic carbon ion radiotherapy beam at the Heavy Ion Medical Accelerator in Chiba, Japan, matching the radiation quality delivered to the normal tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 66 publications
2
14
0
Order By: Relevance
“…The greater carcinogenesis effects of HZE particle radiation have been analyzed from the viewpoint of a targeted effect (genetic change) and nontargeted effects. C-ioninduced lymphomas showed a marginal increase in the frequency of large interstitial deletions at various sites across the genome when compared with that of photon-induced lymphomas [133]. HZE particle irradiation promoted more aggressive cancers, such as increased growth rate, transcriptomic signatures, and metastasis when using a radiation/genetic mammary chimera mouse model of breast cancer [134].…”
Section: Genome Instabilitymentioning
confidence: 91%
“…The greater carcinogenesis effects of HZE particle radiation have been analyzed from the viewpoint of a targeted effect (genetic change) and nontargeted effects. C-ioninduced lymphomas showed a marginal increase in the frequency of large interstitial deletions at various sites across the genome when compared with that of photon-induced lymphomas [133]. HZE particle irradiation promoted more aggressive cancers, such as increased growth rate, transcriptomic signatures, and metastasis when using a radiation/genetic mammary chimera mouse model of breast cancer [134].…”
Section: Genome Instabilitymentioning
confidence: 91%
“…Indeed, concerning carbon ions, literature on secondary tumors is still poor but a study pointed out that 30% of patients treated for cervical cancers developed distant metastases [63]; a case was reported of a brain tumor induced by heavy particle radiotherapy [64]. Preclinical studies, recently performed on mice exposed to carbon ions in comparison to photons, revealed that interstitial chromosome deletions were more increased in secondary cancers induced by carbon exposure [65]. They contradict previous results of Ando et al [66] showing the same induction in carbon locally irradiated mice of secondary tumors after γ-rays.…”
Section: Toxicity Encountered In Patients After Proton or Carbon Ion mentioning
confidence: 99%
“…After controlling for the effect of radiation dose, the relationship between the type of first cancer and the risk of second cancers is much diminished (reviewed in [ 33 ]), although there remain some associations which might be explained by combined effects of concurrent chemotherapy or other treatment differences, selection effects, or inherent genetic susceptibility or shared etiology. Research into identifying radiation signatures in radiotherapy-induced cancers [ 35 , 36 , 37 ] would increase the sensitivity of epidemiology analyses by helping to differentiate between the background of spontaneous second cancers.…”
Section: Observed Susceptibility To Radiation-induced Cancermentioning
confidence: 99%